Fungsi Dewan Perwakilan Rakyat Papua Dalam Pengawasan Otonomi Khusus Bagi Provinsi Papua - Arteza, Muhammad Fardan; Farhan Nafis, Muhammad Ilham; Rambe, Muhammad Naufal Fawwazi; Berbudi, Muhammad Aulia; Akhiruzaman, Emiral Ardhi; Darmawan, Ivan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Papua DPR, the legislative body in Papua, oversees the implementation of special autonomy in the country. However, the Papua Province Development Index is still below expectations, with special autonomy funds amounting to 98.395 trillion. The Papuan DPR has an important role in supervising special autonomy, with four mechanisms in place: responding to community aspirations, working meetings, working visits, and following up on results. The implementation of the Papua DPR is considered less than optimal with problems such as inadequate fund management, local elites seeking profit, and inadequate use of technology. The success of Special Autonomy for Papua depends on the performance of the DPR in supervising, managing and implementing it. The DPR must guarantee transparency, accountability, and appropriate use of funds, as well as the active participation of the Papuan people in the decision-making process. Despite receiving Special Autonomy funds amounting to IDR 1.3 trillion since 2002, the use of these funds has given rise to corruption and the legitimacy of KKN by objectifying community poverty. A comprehensive evaluation of the implementation of Special Autonomy is needed to resolve problems such as infrastructure development, education, economy and health of indigenous Papuans. Corrective action is needed to ensure the effective and efficient use of special autonomy funds and improve the welfare of the Papuan people.